Forensic Anthropology: Morphometric Study of The Sternum Using Computed Tomography Scan to Differentiate Sex Across Various Countries (Literature Review) - Toisuta, Chrisma Virginia; Abid, Istiana Firqah (Photon: Jurnal Sain dan Kesehatan, 2025)
The discovery of bodies in Indonesia is a frequent occurrence. Identifying these bodies requires determining the gender, height, and other physical characteristics to narrow down the search for the victim's identity. Computed tomography (CT) is the modality of choice for evaluating the anatomical details and pathological conditions of the sternum, sternoclavicular joints, and surrounding soft tissues. Given this issue, the researchers were interested in conducting a literature review on morphometric studies of the sternum using computed tomography scans to differentiate gender in various countries. The research method employed was descriptive observational, utilizing a literature review design from several articles published within the last 15 years. The articles selected for this study were based on specific inclusion and exclusion criteria set by the researchers. A total of 20 articles were used in this study. The literature review shows that the increasing number of morphometric studies, particularly in different populations, provides valuable data for researchers. CT can be utilized for the morphometric analysis of living subjects or discovered bones. If parts of the skeleton, such as the pelvis or skull, are not found or are damaged, forensic specialists and forensic anthropologists can accurately estimate gender using the sternum.